Some Coating Properties of Black Alder Wood as a Function of Varnish Type and Application Method - SALCA Emilia-Adela; KRYSTOFIAK Tomasz; LIS Barbara; MAZELA Bartolomiej; PROSZYK Stanislaw (BIORESOURCES, 2016)
The objective of this study was to evaluate the adhesion strength and glossiness of black alder wood (Alnus glutinosa Gaertn. L.) coated with water-borne and UV varnishes by two application systems. Prior to coating, the samples were prepared by sanding with four combinations of grit size sandpapers, 180 being the final grit. The surface quality of the specimens was measured with a white light profilometer. Any increase in grit size gradually reduced surface roughness, which further influenced the overall coating performance of the samples. UV varnish applied by roller presented higher adhesion strength and gloss as compared to spraying. The specimens varnished with a water-borne finish by spraying exhibited a better adherence to the substrate than those of UV varnished samples by the same method and provided glossiness at 60° geometry in the same range. These results are valuable for the furniture manufacturing industry for generating a better use and efficiency of secondary wood resources in order to achieve value-added products
The objective of this study was to evaluate the adhesion strength and glossiness of black alder wood (Alnus glutinosa Gaertn. L.) coated with water-borne and UV varnishes by two application systems. Prior to coating, the samples were prepared by sanding with four combinations of grit size sandpapers, 180 being the final grit. The surface quality of the specimens was measured with a white light profilometer. Any increase in grit size gradually reduced surface roughness, which further influenced the overall coating performance of the samples. UV varnish applied by roller presented higher adhesion strength and gloss as compared to spraying. The specimens varnished with a water-borne finish by spraying exhibited a better adherence to the substrate than those of UV varnished samples by the same method and provided glossiness at 60° geometry in the same range. These results are valuable for the furniture manufacturing industry for generating a better use and efficiency of secondary wood resources in order to achieve value-added products